The Influence of Taste and Price on Re-Purchase Intentions of Mie Gacoan in Jombang - Nur Alful Lailiyah; Wisnu Mahendri (INCOME: Innovation of Economics and Management, 2024)
This study investigates the influence of taste and price on the re-purchase intentions of customers at Mie Gacoan in Jombang. The culinary industry in Indonesia is highly competitive, with businesses needing to continuously innovate and improve to maintain customer loyalty. Using a quantitative approach, this research sampled customers who have visited or ordered from Mie Gacoan. Primary data were collected through surveys and analyzed using statistical methods, including multiple regression analysis. The findings indicate that both taste and price significantly impact customers' intentions to repurchase, with taste having a slightly stronger influence. These results provide valuable insights for business strategy, particularly in enhancing customer retention through the quality of taste and competitive pricing.